Påverkan av gruvdrift på sedimentegenskaper och toxicitet för akvatiska organismer i norra Sverige - Lidman, Johan; Olid, Carolina; Bigler, Christian; Berglund, Åsa (Umeå University, 2023)
The data contain information on spatial and temporal variation in sediment properties and toxicity estimates of three lakes in close proximity to an abandoned Pb/Zn-mine. One sediment profile per lake was analyzed and the age of different sediment layers was estimated, to be able to correlate the results with known activities during the development of the mine.

Number of variables: 17
Number of rows (incl. header): 76

Variable List:
Site: Lake origin of the sediment core (Lake 1, Lake 2 or Lake 3)
Depth: Depth of the analyzed sediment layer (cm) for each core
Zn: Zinc concentration in the sediment layer (mg kg-1)
Pb: Lead concentration in the sediment layer (mg kg-1)
Density: Density of the sediment layer (g cm-3)
LOI: Loss on ignition for each sediment layer (%)
TOC: Total organic carbon for each sediment layer (%)
PECQ: Predicted effect concentration quotient for each sediment layer
PECQ.norm: Predicted effect concentration quotient for each sediment layer, normalized to total organic carbon content
210Pb: 210Pb activity for each sediment layer (Bq kg-1), measured at 46.5keV
SD(210Pb): Standard deviation of 210Pb activity for each sediment layer (Bq kg-1), measured at 46.5keV
214Pb(295keV): 214Pb activity for each sediment layer (Bq kg-1), measured at 295keV
SD(295keV): Standard deviation of 214Pb activity for each sediment layer (Bq kg-1), measured at 295keV
214Pb(351 keV): 214Pb activity for each sediment layer (Bq kg-1), measured at 351keV
SD(351 keV): Standard deviation of 214Pb activity for each sediment layer (Bq kg-1), measured at 351keV
137Cs: 137Cs activity for each sediment layer (Bq kg-1), measured at 662keV
SD(137Cs): Standard deviation of 137Cs activity for each sediment layer (Bq kg-1)

Missing data codes: NA – not analyzed

Data innefattar spatiala och temporala variationer i sedimentegenskaper och estimerad toxicitet i tre sjöar nära en nedlagd Pb/Zn-gruva. En sedimentprofil per sjö analyserades och de olika sedimentlagrens ålder bestämdes, för att kunna korrelera resultaten med utvecklingen av gruvan.

Antal variabler: 17
Antal rader (inkl. rubrikrad): 76

Lista på variabler:
Site: Sjöidentitet på sedimentprofilen (Lake 1, Lake 2 or Lake 3)
Depth: Djup på de analyserade sedimentlagren (cm) för varje profil
Zn: Zinkkoncentrationen i respektive sedimentlager (mg kg-1)
Pb: Blykoncentrationen i respektive sedimentlager (mg kg-1)
Density: Densitet i varje sedimentlager (g cm-3)
LOI: Glödförlust i varje sedimentlager (%)
TOC: Totalhalt organiskt kol (%)
PECQ: Predicted effect concentration quotient
PECQ.norm: Predicted effect concentration quotient, normaliserad för TOC
210Pb: 210Pb aktiviteten (Bq kg-1), analyserad vid 46.5keV
SD(210Pb): Standardavvikelsen för 210Pb aktiviteten (Bq kg-1)
214Pb(295keV): 214Pb aktiviteten (Bq kg-1), analyserad vid 295keV
SD(295keV): Standardavvikelsen för 214Pb aktiviteten (Bq kg-1), analyserad vid 295keV
214Pb(351 keV): 214Pb aktiviteten (Bq kg-1), analyserad vid 351keV
SD(351 keV): Standardavvikelsen för 214Pb aktiviteten (Bq kg-1), analyserad vid 351keV
137Cs: 137Cs aktiviteten (Bq kg-1), analyserad vid 662keV
SD(137Cs): Standardavvikelsen för 137Cs aktiviteten (Bq kg-1)

Missing data codes: NA – not analyzed
Effect of past century mining activities on sediment properties and toxicity to freshwater organisms in northern Sweden
Keywords: mining; ecotoxicity; miljötoxicitet; freshwater; sötvatten; freshwater organism; sötvattensorganism; freshwater pollution; förorening av sötvatten; heavy metal; tungmetall; lake; sjö; mine; gruva; sediment; sediment; Environmental Sciences; Miljövetenskap; Geoscientific Information; Geovetenskap